Comparison between ultrasonography and MRI in diagnosis of knee joint meniscal injuries - Ibrahem Elsayed Abdellatif Abuomira; Yasser Abdelaal Ahmed; Mohamed Taha Abd Elghafar Elshahat (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Meniscal tears are one of the most frequent disorders affecting the knee joint in athletes and normal people. MRI the first choice of imaging of knee joint but in recent days, ultrasound (US) has made strides in imaging of musculoskeletal disorders due to improvement of imaging qualities. This study aimed to investigate the role of US in diagnosis of meniscus tears as compared to MRI. Patients and Methods A total of 100 patients examined by high definition US and under go to MRI examination of the knee joint. Results Regarding the diagnostic performance of US compared to MRI, the sensitivity reached (89.1%), specificity (∼72.2%), positive predictive value (∼90.1%), negative predictive value (70.1%), and accuracy (84.7%). Conclusion Ultrasonography may be used as a screening tool before arthroscopy in selected cases where MRI was a contraindication or is not available or if the patient was not affording. Ultrasonography showed a dynamic image of the meniscus and thus may prove useful if studied in conjunction with correct clinical examination.